Assessing Salmonella enterica burden and control measures in dairy cattle - Edache, Stephen Ejembi (Kansas State University, 2023)
Salmonella enterica stands as an important pathogen of significant public health concern, given its widespread prevalence and distribution. Its presence has been notably identified not only in the feces and on the hides of cattle but also, of recent paramount importance, within their lymph nodes (LN). This significant concern surrounding Salmonella in cattle forms the basis for Chapter 1 of this thesis which consists of a comprehensive review of the literature on the epidemiology and microbiological characteristics of Salmonella in cattle. This chapter encompasses various aspects, including the prevalence and concentration of Salmonella in different cattle samples, the risk factors affecting its prevalence and concentration estimates, and the various intervention strategies established with the aim of mitigating this pathogen in cattle. Chapter 2 presents up-to-date information on Salmonella prevalence estimates, serotype diversity, and antimicrobial-resistant isolates in cattle LN, as well as the effectiveness of a control measure, across different seasons and multiple regions within the U.S., from an observational study. Briefly, the objectives were 1) to determine whether a larger scale or farm-level use of a commercially available postbiotic product (Nutritek™ (Diamond V, Cedar Rapids, Iowa, U.S.)) compared to not feeding a postbiotic product (i.e., No-postbiotic) was associated with the reduction in the prevalence and concentration of Salmonella organisms in the subiliac LN of cull dairy cows, across seasons and regions, harvested in two large U.S. commercial processing plants (Study 1), 2) to determine associations between cattle type, other demographic and management characteristics, season, plant and region with prevalence and concentration of Salmonella in bovine LN (Study 1), and 3) to provide a baseline estimate of the Salmonella LN prevalence and serovar diversity from cull dairy cattle obtained from suppliers in different U.S. regions and seasons (Study 2). In collaboration with two commercial processing plants in the Southwestern (SW) and Northeastern (NE) regions of the U.S., cull dairy cattle lots processed in the same week from dairy farms that fed the postbiotic or did not feed the postbiotic (No-postbiotic) were identified and sampled (Study 1). For the baseline prevalence study, LN samples from dairy farms supplying cattle to five processing plants in four regions (Upper Midwest, Midwest, Northeast, and Southwest) were collected (Study 2). Up to 20 LN were collected from each supplier farm at least once every season, for both studies. Samples were analyzed for Salmonella by culture-based and quantitative PCR methods. Isolates were subjected to serotype identification via a classical serotyping and molecular typing, as well as to antimicrobial susceptibility testing using the broth micro-dilution method. Although a numerical reduction was observed, the dairy farm administration of a postbiotic product at pre-harvest was not effective at significantly reducing Salmonella prevalence in LN of cull dairy cattle. Salmonella LN prevalence only significantly varied by region/processing plant, where the Southwest region showed a higher prevalence than its Northeast counterpart. These findings were consistent with the baseline evaluation of Salmonella LN prevalence in cull dairy cattle across different U.S. regions and seasons, where region and season were the main drivers of prevalence. Within Study 1, dominant serotypes included Montevideo, Mbandaka, Muenster, Cerro, Meleagridis, and Anatum. The probability of isolating a Salmonella serotype did not significantly vary by feed additive status or region, however, it did vary by season. Between 0 and 34 isolates exhibited resistance to each antimicrobial, with streptomycin and ciprofloxacin showing the highest number of resistant isolates, although resistance to these antimicrobials did not significantly vary by feed additive status, region, or season. There were seven isolates that were considered multidrug-resistant (MDR); one of the MDR isolates belonged to a sample from a postbiotic supplier from the Northeast region, whereas the remaining six isolates were from No-postbiotic samples, five from the Southwest and one from the Northeast region. In Study 2, dominant serotypes included Montevideo, Muenster, Mbandaka, Anatum, and Cerro. As with Study 1, the probability of isolating a Salmonella serotype did not significantly vary by region, but it did vary by season. For each antimicrobial, there were between 0 and 35 isolates that exhibited a resistant phenotype, with streptomycin showing the highest number of resistant isolates, although resistance to streptomycin did not significantly vary by season or region. There were four isolates that were considered MDR; two of the MDR isolates belonged to a sample from the Southwest region, one from the Upper Midwest, and one from the Northeast region. Chapter 3, the discussion chapter, serves as a synthesis of the insights garnered from the preceding chapters. Beyond illustrating the significance of the information presented in chapters 1 and 2 for the beef industry and public health at large, the discussion chapter delves into future directions. It highlights the necessity of acquiring a comprehensive understanding of the routes of entry, infection mechanisms, and the persistent survival of Salmonella, particularly within the confines of the LN. This understanding may prove pivotal in shaping effective intervention strategies aimed at mitigating Salmonella contamination in beef. Ultimately, these strategies are essential for ensuring food safety and safeguarding public health.
Keywords: Food safety; Salmonella; Prevalence; Dairy cattle; Postbiotic; Subiliac lymph nodes